2016
DOI: 10.1080/10245332.2015.1106814
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase and regulatory T cells in acute myeloid leukemia

Abstract: In this study, we revealed an association between high IDO expression in MSCs and elevated levels of Tregs which could have an important role in the pathogenesis of AML, providing immunosuppressive microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…A positive correlation was found between high IDO1 expression in bone marrow-derived mesenchymal stem cells and elevated percentage of T reg cells in acute myeloid leukemia [69]. Therefore, the proportion of CD4 + CD25 + CD39 + T reg cells was analyzed in PMBCs at baseline, during and after BCG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between high IDO1 expression in bone marrow-derived mesenchymal stem cells and elevated percentage of T reg cells in acute myeloid leukemia [69]. Therefore, the proportion of CD4 + CD25 + CD39 + T reg cells was analyzed in PMBCs at baseline, during and after BCG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are stromal cells which define the bone marrow microenvironment and give rise to other supporting cells. MSCs highly express IDO, which correlates with expansion of Tregs and could inhibit CAR T cell effector function (117).…”
Section: Bone Marrow Nichementioning
confidence: 99%
“…Mansour et al [41] High IDO expression in mesenchymal stem cells and increased levels of T-regs play pivotal role in the pathogenesis of AML combination with CY was recommended by them as an effective IDO-positive lymphoma treatment. These findings suggest that inhibition of IDO might offer a therapeutic approach for lymphoma.…”
Section: Ido In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…IDO is involved in immune system regulation. IDO upregulation is associated with poor prognosis in various cancers [20,30,34,35,39,41,43,51] but few studies suggested that increased expression of IDO was linked with favourable prognosis. [19,46] Further studies are required in view of the contradictory findings, to comprehend this complex role of IDO in various cancers.…”
Section: Ido As An Immunotherapeutic Targetmentioning
confidence: 99%